Morfoanatomia comparada de Allagoptera campestris (Mart.) Kuntz e Allagoptera brevicalyx M. Moraes (Arecaceae) - Barros, Ariana Ceolin, 1998- (2020)
Orientador : Professor Dr. Bruno Francisco Sant’Anna dos Santos